Efektivitas Pelaksanaan Kajian Lingkungan Hidup Strategis (KLHS) dalam Perencanaan Tata Ruang Kota Salatiga - Wijayanto, Paulus Bimo; Maryono, Maryono (Universitas Diponegoro, Indonesia, 2021)
Strategic Environmental Assessment (SEA) is a process by evaluating environmental impacts and ensuring that the principles of sustainability are integrated in decision making. Strategic Environmental Assessment (SEA) in Indonesia is regulated in a law stipulated by the government which stipulates that it is the duty of both the government and local governments to carry out both development planning and spatial planning. Salatiga City in spatial planning in accordance with the existing guidelines implements SEA, namely in making the Regional Spatial Plan and Detailed Spatial Plan. The rules and policies that are continuously updated by the government regarding the procedures for implementing SEA require understanding from stakeholders who have an interest in Policies, Plans and Programs (KRP) in spatial planning in Salatiga City, with good quality understanding by stakeholders can ensure that the stages of implementing SEA running well and integrating SEA into the KRP spatial planning that ensures environmental damage can be minimized. The purpose of this research is to examine the effectiveness of the implementation of SEA in spatial planning in the city of Salatiga and it is hoped that it can provide alternative steps for implementing SEA which can be used as a direction in the implementation of SEA based on existing facts and conditions. The data used in this study consist of primary data and secondary data which refer to the SEA implementation tools, namely Rules and Policies, Documents and Reports, Institutional Tools, Implementation Standard Operating Procedures, Monitoring, Evaluation and Feedback. The research method used is a mixed method research by combining qualitative and quantitative analysis. From the results of the analysis, it can be seen that the implementation of SEA in the City of Salatiga in spatial planning still needs to be considered in order to run effectively, even though the resulting SEA process has adjusted to the existing regulations but still in activities such as monitoring, evaluation and feedback still need to be carried out in an effective manner. maximum because these activities constitute control over decision making in Activities, Plans and Programs in the resulting spatial planning and stakeholder understanding of the institutional instruments of SEA in Salatiga City still need to be improved because not all existing instruments are understood and are still in a category that is not all in categories really understand evenly so that steps are needed that are adjusted to the existing conditions in an effort to increase the effectiveness of the implementation of SEA so that the resulting SEA can run effectively and maximally.